2004
DOI: 10.1556/abiol.55.2004.1-4.18
|View full text |Cite
|
Sign up to set email alerts
|

The early snail acquires the learning. Comparison of scores for conditioned taste aversion between morning and afternoon

Abstract: The pond snail Lymnaea stagnalis acquires conditioned taste aversion (CTA) and maintains its memory for more than a month. Snails in our laboratory were cultured at 20 degrees C on a 12:12 light-dark cycle (light from 7 am to 7 pm). To examine the hours during which snails acquire CTA effectively, we trained some snails in the morning and others in the afternoon, and then compared their scores. CTA developed in both cases, but scores were significantly better in the morning than in the afternoon. To elucidate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…3; Wagatsuma et al, 2004;Ito et al, 2012Ito et al, , 2015. Briefly, all snails were first given a pretest in polystyrene Petri dishes (diameter 35 mm).…”
Section: Taste Aversion Training (Cta) Proceduresmentioning
confidence: 99%
“…3; Wagatsuma et al, 2004;Ito et al, 2012Ito et al, , 2015. Briefly, all snails were first given a pretest in polystyrene Petri dishes (diameter 35 mm).…”
Section: Taste Aversion Training (Cta) Proceduresmentioning
confidence: 99%
“…Our previously published work tended to focus on group data and on experimental procedures optimized to produce consistent learning and LTM formation (Kojima et al, 1996;Wagatsuma et al, 2004). Thus, individual differences in learning and memory capabilities between subjects were not a major focus.…”
Section: Motivation On Conditioned Taste Aversionmentioning
confidence: 99%
“…The sea hare (Aplysia californica) and the great pond snail (Lymnaea stagnalis) are now well established as animal models of learning and memory (Kandel, 2001;Lukowiak et al, 2006). Recent studies have demonstrated an influence of the circadian timing system in learning and memory formation in these species (Fernandez et al, 2003;Wagatsuma et al, 2004), but they have not been well studied in the context of sleep. Indeed, it has not yet been determined whether these molluscs do in fact sleep.…”
Section: Introductionmentioning
confidence: 99%